Analysis on background subtraction for street surveillance - Zainuddin, N. Afiqah; Mohd Mustafah, Yasir; Azman, Amelia Wong; Rashidan, M. Ariff; A. Aziz, Nor Nadirah (2014)
Background subtraction is a well-known technique used in computer vision applications. However, in public surveillance system, the utilization of background subtraction still new and far from being solved. Insufficient analysis of the background subtraction algorithms made the situation getting worse. The analysis of the commonly-used algorithms is presented in this paper. Experiments are conducted to quantitatively evaluate the performance of the algorithms by using three video sequences. The more suitable algorithm for various conditions is expected to be presented as the results in this paper.